Sustainability-based performance evaluation of hybrid nanofluid assisted machining. (1st June 2020) - Khan, Aqib Mashood; Jamil, Muhammad; Mia, Mozammel; He, Ning; Zhao, Wei; Gong, Le
Abstract: China's industrial sector accounts for more than half of the country's total energy demand. During 2010–2012, nearly 73% of the total hike in the global carbon emission has occurred in China alone. According to the regulations of the International Organization for Standardization, the material processing industry is required to cut down the energy consumption demand and carbon emission. It is worthwhile to consider the elimination of cutting fluids from the machining domain for reducing production cost and environmental impact. This study presents component-stage based holistic models of energy, cost, and carbon emission. The models are validated through the experimental data obtained from turning of Haynes 25 alloy conducted under nanofluid (alumina-graphene) assisted minimum quantity lubrication. The data for energy consumption, cost, and CO2 emission are obtained from the experimental work and literature. The results show that the feed rate possesses the most significant effect on energy consumption. The shares of the work material's choice in total energy consumption, carbon emission, and total cost are found to be 93.7%, 66.8%, and 56.2%. The nanoparticles share a small portion of the total cost per unit product. The Environmental Performance Index (EPI) obtained in this study reveals a strong possibility of the industrial application of nanofluids in machining. This study also preaches "think green, plan green, and go green." Graphical abstract: Image 1 Highlights: Holistic models for process time, power, energy consumption, cost and CO2 . The cumulative energy demand in hybrid nanofluid based turning Hayness 25. CO2 emissions have been characterized in turning process under hybrid nanofluid. The influence of nanoparticle concentration quantity used on CED. Environmental performance of Al-Gnp hybrid nanofluid is shown to be high.